Synthesis and characterisation of ternary system LiCoPO4-LiNiPO4-LiMnPO4 cathode materials for Li-ION batteries - Tan, Tze Qing (School of Materials Engineering, Universiti Malaysia Perlis, 2018)
The research objectives are to determine the solid solution limit at high temperature for the series of LiCo1-x[Ni0.5Mn0.5]xPO4, LiNi1-x[Co0.5Mn0.5]xPO4 and LiMn1-x[Co0.5Ni0.5]xPO4 (0 d x d 1) ; to estimate the amount of anti-site defects in LiCo1-x[Ni0.5Mn0.5]xPO4, LiNi1-x[Co0.5Mn0.5]xPO4 and LiMn1-x[Co0.5Ni0.5]xPO4 (0 d x d 1) using Rietveld refinement ; to investigate theeffects of different doping concentrations and cooling conditions on the structural and electrical properties of LiCo1-x[Ni0.5Mn0.5]xPO4, LiNi1-x[Co0.5Mn0.5]xPO4 and LiMn1-x[Co0.5Ni0.5]xPO4 (0 d x d 1) ; to justify the effect of particles size reduction and carbon coatingon the conductivity of modified LiNi1/3Mn1/3Co1/3PO4/C ; to evaluate the effects of Zn substitution on the structural and electrochemical properties of Li2CoMn3O8 (Li2Co1-xZnxMn3O8).